Penerapan MIcrosoft Excel Keuangan Dan perpajakan Untuk Meningkatkan Akurasi Pelaporan Keuangan Dan Kepatuhan Pajak Pada Umkm Hp Tofa - Eri Bestary Al haitamy; Ivan Ramadhan; Indra gunawan (LP2M Politeknik Jambi, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the economy; however, many MSMEs still have difficulties in preparing proper financial records. UMKM Servis HP Tofa is a service-based business that previously used manual bookkeeping, resulting in unstructured financial reports and low tax compliance. This study aims to describe the implementation of a simple Microsoft Excel–based accounting system, analyze its impact on financial reporting accuracy and tax compliance, and identify factors influencing its effectiveness. This research uses a descriptive qualitative method with data collected through observation, interviews, and documentation. The accounting system was designed using Microsoft Excel based on SAK EMKM and the 0.5% Final Income Tax regulation for MSMEs. The results show that the Excel-based system helps MSMEs prepare more organized, accurate, and understandable financial reports. In addition, the system simplifies tax calculation and reporting, which improves tax awareness and compliance. The effectiveness of the system is influenced by basic accounting knowledge, ease of use of Excel, and consistency in recording transactions.